Optimization Study of Power Plant Direct Flow Cold-end Subsystem Based on Negative Digging - CHEN Yun; LI Sen; ZHAO Yuanbin (发电技术, 2022)
In view of the unstable performance of the cold-end system of traditional power plants and the high annual operating cost, a mathematical model based on the heat, resistance, civil construction and annual operating cost calculation of the direct flow cold end system based on negative digging depth was established, and the cold end system configuration was obtained from different conditions outside the tower. The optimal configuration was used to analyze the effect of cooling water for intlet tower water temperature, coagulator area unit price and condenser negative digging depth on the performance of cold end system. The results show that reducing the cooling water for intlet tower water temperature and condenser area unit price can reduce the annual operating cost of cold end system. The performance parameters of the cold end system with a negative digging depth of 3 to 5 m reach the lager value. Therefore, selecting the cold end system configuration according to different weather parameters outside the tower can improve the operating efficiency of the power plant and reduce the annual operating cost of the cold end system.